2019
DOI: 10.1038/s41417-019-0101-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeted AAVP-based therapy in a mouse model of human glioblastoma: a comparison of cytotoxic versus suicide gene delivery strategies

Abstract: Glioblastoma persists as a uniformly deadly diagnosis for patients and effective therapeutic options are gravely needed. Recently, targeted gene therapy approaches are re-emerging as attractive experimental clinical agents. Our ligand-directed hybrid virus of adeno-associated virus and phage (AAVP) is a targeted gene delivery vector that has been used in several formulations displaying targeting ligand peptides to deliver clinically applicable transgenes. Here we compared different constructs side-by-side in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 34 publications
(55 reference statements)
2
32
0
Order By: Relevance
“…These results confirm that gene delivery by AAVP and the expression of the S protein in the draining lymph nodes trigger a systemic S protein-specific humoral response. Moreover, the data recapitulate the well-established attribute of AAVP particles in preventing off-target effects, even upon clearance via the reticulum-endothelial system (RES), sparing non-targeted or distal tissues, while a strong promoter drives the expression of the transgene in the transduced cells (20, 23-28). This finding is particularly important for evaluating potential adverse effects in novel, candidate AAVP-based vaccines, since off-site transduction-associated toxicities have been reported in toxicological studies of adenovirus vaccines (48, 49).…”
Section: Resultssupporting
confidence: 60%
“…These results confirm that gene delivery by AAVP and the expression of the S protein in the draining lymph nodes trigger a systemic S protein-specific humoral response. Moreover, the data recapitulate the well-established attribute of AAVP particles in preventing off-target effects, even upon clearance via the reticulum-endothelial system (RES), sparing non-targeted or distal tissues, while a strong promoter drives the expression of the transgene in the transduced cells (20, 23-28). This finding is particularly important for evaluating potential adverse effects in novel, candidate AAVP-based vaccines, since off-site transduction-associated toxicities have been reported in toxicological studies of adenovirus vaccines (48, 49).…”
Section: Resultssupporting
confidence: 60%
“…HSV-1 TK, but not mammalian TK, effectively phosphorylates these analogues, which leads to their incorporation into DNA, premature replication termination and as a result induces apoptotic cell death [ 11 ]. Importantly, the suicide gene therapy application gives rise to the “bystander effect”, which is that a higher percentage of tumor cell death occurs with a lower percentage of transfected cells [ 12 , 13 , 14 ]. This phenomenon increases the efficacy of the suicide gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, αvβ3 integrins are significantly upregulated in uterine leiomyoma cells as compared to normal myometrium that makes this receptors perspective for targeted gene therapy of UL [ 35 ]. Linear RGD and different cyclic RGD-ligands have been developed and actively studied for tumor targeting [ 2 , 14 , 36 , 37 , 38 , 39 ]. Compared to linear RGD sequences, cyclic ones favor in selectivity and stability and are widely used for strong binding to αv-integrins.…”
Section: Introductionmentioning
confidence: 99%
“…Upon cell entry of the hybrid RGD4C/AAV-phage (RGD4C/AAVP), the AAV transgene cassette is released, resulting in gene expression in tumors from a cytomegalovirus, CMV , promoter [ 5 , 6 ]. We have reported that this vector targets numerous cancer models in vivo upon intravenous delivery [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. A study in pet dogs with spontaneous cancers proved the safety of repeated vector dosing, resulting in complete tumor eradication in a few dogs with aggressive cancers [ 20 ].…”
Section: Introductionmentioning
confidence: 99%